1)-6x-13=-7x-14
2)5x=8+3(2x+3)
3)3(4x+1)+3x=2x-23
4)7(2x-5)-4 (5x+3)=-33
5)6x-7 (3x-5)-2(4x-7)=3
6)12(x-2)-(4x-3)=8 (x+3)​

Derety11 Derety11    2   16.01.2020 20:29    5

Ответы
VTKOF VTKOF  11.10.2020 01:15

Пошаговое объяснение:

1)-6x-13=-7x-14

 -6x+7x=-14+13

  x=-1

2)5x=8+3(2x+3)

  5x=8+6x+9

  5x-6x = 17

  x=-17

3)3(4x+1)+3x=2x-23

  12x+3+3x=2x-23

  12x+3x-2x=-23-3

  13x= -26

  x=-2

4)7(2x-5)-4 (5x+3)=-33

  14x-35-20x-12=-33

  14x-20x=-33+35+12

  -6x = 14

   x= -14/6

5)6x-7 (3x-5)-2(4x-7)=3

  6x-21x+35 -8x+14=3

  6x-21x-8x=3-35-14

  -23x = -46

   x=2

6)12(x-2)-(4x-3)=8 (x+3)​

  12x-24-4x+3=8x+24

   12x-4x-8x=24+24-3

   0x = 45

нет решения

ПОКАЗАТЬ ОТВЕТЫ
sevara221 sevara221  11.10.2020 01:15

1)-6x-13=-7x-14

7x-6x=13-14

x=-1

ответ: х=-1

2)5x=8+3(2x+3)

5x=8+6x+9

5x-6x=8+9

-x=17

x=-17

ответ: х=-17

3)3(4x+1)+3x=2x-23

12x+3+3x=2x-23

12x+3x-2x=-23-3

13x=-26

x=-2

ответ: х=-2

4)7(2x-5)-4(5x+3)=-33

14x-35-20x-12=-33

14x-20x=35+12-33

-6x=14

x=-14/6

ответ: х=-14/6

5)6x-7(3x-5)-2(4x-7)=3

6x-21x+35-8x+14=3

6x-21x-8x=3-35-14

-23x=-46

x=2

ответ: x=2

6)12(x-2)-(4x-3)=8(x+3)

12x-24-4x+3=8x+24

12x-4x-8x=24+24-3

0=45

ответ: корней нет

Пошаговое объяснение:

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика